Remote Sensing of Atmospheric Pollution - Yang Liu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This book edited by Drs. Yang Liu from Emory University, Jun Wang from the University of Iowa, and Omar Torres from NASA Goddard Space Flight Center recompiles the results of recently documented research work on Atmospheric Pollution published as a special issue of the MDPI Remote Sensing Journal. It includes twenty peer-reviewed scientific articles on Remote Sensing of Atmospheric Pollution by leading experts from research institutions and universities around the world. The quality and scientific relevance of the published material was carefully monitored by the guest editor team. Both modeling and observational aspects of particulate matter and trace gas pollutants are treated in great detail by the contributing experts. Many of the published articles explore the use of satellite observations by sensors such as MODIS, VIIRS, and OMI as a valuable research tool. Authors use these observations in combination with models and ground-based observations to enhance the resources available to improve our understanding of the physical and chemical processes driving the observed pollution levels near the ground and in the free troposphere that ultimately determine the quality of the air we all breathe. This is an important reference book for scientists, professors and students both graduate and undergraduate interested in up-to-date survey of remote sensing applications to Atmospheric Pollution.